The complete IDIOT'S guide to saving the environment - Pahl, Greg (Alpha Books, 2001)
The environmental movement and rising awareness of global warming have sparked an interest in green living. People want to know what they can do to live sustainable lives. In this book, you will find an overview of global warming and environmental degradation of air, water, and soil; what sustainable living is and how to do it; how to cut down on carbon output (the cause of global warming) with alternative cars and fuels; and environmentally friendly home and lawn care products.